Underweight Nutritional Status as a Predictor of Mortality in Alzheimer's Disease : A Systematic Review and Meta-Analysis of Prospective Cohort Study - Kemal Akbar Suryoadji; Muhammad Faruqi; Vincentius Juan Aryaputra (Cermin Dunia Kedokteran, 2022)
Purpose: The research was conducted to determine the risk of mortality in underweight Alzheimer's disease patients and to consider nutritional maintenance as an important management approach in Alzheimer’s patients. Methods: This review used publications found in Pubmed, Scopus, Cochrane, and ScienceDirect. The keywords were “((Alzheimer's Diseased) AND (Underweight) AND (Mortality))”. Meta-analysis review with Revman 5 software calculated the average relative risk from all selected cohort studies. Result: The process identify 230 articles, only three studies with 1423 patients were included. The meta-analysis result showed that based on their BMI status, underweight patients have a higher risk of mortality than normal weight patients. (RR: 1.65, 95% CI: 1.32-2.06). Conclusion: Underweight nutritional status in Alzheimer's patients increases the risk of mortality compared to the individuals with normal nutritional status.Tujuan: Penelitian ini dilakukan untuk menentukan risiko kematian pasien penyakit Alzheimer yang memiliki berat badan kurang dan mempertimbangkan pemeliharaan nutrisi sebagai bagian dari pendekatan tata laksana pasien Alzheimer. Metode: Tinjauan dalam publikasi ini diambil dari Pubmed, Scopus, Cochrane, dan ScienceDirect. Kata kunci yang digunakan ialah “((Alzheimer Diseased) AND (Underweight) AND (Mortality))”. Tinjauan meta-analisis menggunakan perangkat lunak Revman 5 menghitung rata-rata risiko relatif dari semua studi kohort yang dipilih. Hasil: Dari 230 artikel yang berhasil diidentifikasi, 3 studi dengan 1423 pasien dimasukkan dalam studi. Hasil meta-analisis menunjukkan berdasarkan status Indeks Massa Tubuh, bahwa pasien dengan berat badan kurang memiliki risiko mortalitas lebih tinggi daripada pasien dengan berat badan normal (RR: 1.65, 95% CI: 1.32-2.06). Simpulan: Kondisi nutrisi dengan berat badan kurang pada pasien Alzheimer meningkatkan risiko mortalitas dibandingkan dengan individu yang memiliki berat badan normal.